Accountability for past human rights violations: contributions of inter-American organs of protection - Méndex, Juan E. (Social justice, 1999)
Part of a special issue on state terrorism and impunity in Latin America. The writers discuss efforts to account for past human rights violations in the region, focusing on the contributions of the Inter-American Commission and the Inter-American Court of Human Rights—the bodies that implement international human rights law in the region—to that cause. They outline the phenomenon of impunity and the current status of the battle to overcome it. They consider the following affirmative obligations on the state: the obligation to investigate, prosecute, and punish; to disclose to the victims and to society all that can be reliably known about the circumstance of the crime; to offer to the victims or their kin some measure of reparation; and to eliminate from the ranks of the security forces those agents who are known to have taken part in such crimes. They describe the contributions of the commission and the court to each of these four independent obligations.